Making free public healthcare attractive: optimizing health equity funds in Cambodia - Bart Jacobs; Ashish Bajracharya; Jyotirmoy Saha; Chhorvann Chhea; Ben Bellows; Steffen Flessa; Adelio Fernandes Antunes (BMC, 2018)
Abstract Background Following the introduction of user fees in Cambodia, Health Equity Funds (HEF) were developed to enable poor people access to public health services by paying public health providers on their behalf, including non-medical costs for hospitalised beneficiaries (HEFB). The national scheme covers 3.1 million pre-identified HEFB. Uptake of benefits, however, has been mixed and a substantial proportion of poor people still initiate care at private facilities where they incur considerable out-of-pocket costs. We examine the benefits of additional interventions compared to existing stand-alone HEF scenarios in stimulating care seeking at public health facilities among eligible poor people. Methods We report on three configurations of HEF and their ability to attract HEFB to initiate care at public health facilities and their degree of financial risk protection: HEF covering only hospital services (HoHEF), HEF covering health centre and hospital services (CHEF), and Integrated Social Health Protection Scheme (iSHPS) that allowed non-HEFB community members to enrol in HEF. The iSHPS also used vouchers for selected health services, pay-for-performance for quantity and quality of care, and interventions aimed at increasing health providers' degree of accountability. A cross sectional survey collected information from 1636 matched HEFB households in two health districts with iSHPS and two other health districts without iSHPS. Respondents were stratified according to the three HEF configurations for the descriptive analysis. Results The findings indicated that the proportion of HEFB who sought care first from public health providers in iSHPS areas was 55.7%, significantly higher than the 39.5% in the areas having HEF with health centres (CHEF) and 13.4% in the areas having HEF with hospital services only (HoHEF). The overall costs (out-of-pocket and transport) associated with the illness episode were lowest for cases residing within iSHPS sites, US$10.4, and highest in areas where health centres were not included in the package (HoHEF), US$20.7. Such costs were US$19.5 at HEF with health centres (CHEF). Conclusions The findings suggest that HEF encompassing health centre and hospital services and complemented by additional interventions are better than stand-alone HEF in attracting sick HEFB to public health facilities and lowering out-of-pocket expenses associated with healthcare seeking.